2018
DOI: 10.1002/mds.27426
|View full text |Cite
|
Sign up to set email alerts
|

Sustained quality‐of‐life improvements over 10 years after deep brain stimulation for dystonia

Abstract: DBS for dystonia results in long-term quality-of-life improvements that persist on average 10 years or more after surgery. The prevalence of stimulation-induced parkinsonism and cognitive impairment is low. © 2018 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
(89 reference statements)
1
10
1
Order By: Relevance
“…Manifestations of parkinsonism, including bradykinesia and freezing of gait, have been described after chronic pallidal stimulation for dystonia [112][113][114] and may resolve upon using more dorsal contacts [113]. They increase in frequency with age, particularly after the fourth decade [98] and are therefore quite rare in the pediatric population. However, one study in DYT28 pediatric patients treated with GPi DBS reported freezing of gait at 3-6 years post-DBS [84].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Manifestations of parkinsonism, including bradykinesia and freezing of gait, have been described after chronic pallidal stimulation for dystonia [112][113][114] and may resolve upon using more dorsal contacts [113]. They increase in frequency with age, particularly after the fourth decade [98] and are therefore quite rare in the pediatric population. However, one study in DYT28 pediatric patients treated with GPi DBS reported freezing of gait at 3-6 years post-DBS [84].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…We postulate that this could be due to stimulation effects of the contralateral GPi electrode, or direct lesioning effects of the GPi electrodes, or even the sequelae of the disease progression. Hypokinesia following bilateral pallidal DBS has been reported to more likely occur with high‐frequency stimulation and more ventral active contact . Stimulating another target, such as subthalamus, could be considered a possible alternative in this condition …”
Section: Serial Changes In the Severity Of Dystonia And Disability Ramentioning
confidence: 99%
“…Hypokinesia following bilateral pallidal DBS has been reported to more likely occur with high-frequency stimulation and more ventral active contact. 6 Stimulating another target, such as subthalamus, could be considered a possible alternative in this condition. 7 Finally, the subjective improvement in our patient's overall function was not reflected by the BFMDRS disability scale scores, possibly because the improvement in postural stability and pain were not adequately captured.…”
mentioning
confidence: 99%
“…A diagnosis of “primary dystonia” was often the main inclusion criterion, without further differentiation of the genetic background, while patients categorized as “secondary dystonia” were excluded in several studies. The same considerations apply to reports of long‐term follow‐up data on motor outcome and quality of life in DBS patients operated on more than five years ago . Resistance to the new terminology may arise from difficulty in translating this classic terminology to the new.…”
Section: Discussionmentioning
confidence: 99%
“…The recently published guideline for translating from old terminology may facilitate using the new classification for long‐term studies that were designed using the older definitions . There is a general belief that “primary” dystonia has a better post‐surgical outcome compared to “secondary” dystonia . This would be translated to say that idiopathic isolated dystonia has a more favorable outcome than acquired dystonia.…”
Section: Discussionmentioning
confidence: 99%